2018
DOI: 10.3892/etm.2018.5723
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profiles of BMSCs induced into osteoblasts with osteoinductive medium

Abstract: Abstract. MicroRNA (miRNA) plays an important role in cell differentiation and functions as a regulator. Therefore, miRNA is important in the process of bone marrow mesenchymal stem cells (BMSCs) being induced into osteoblasts. In this study, mouse BMSCs were induced with osteoinductive medium, the indices related to osteoblastic differentiation were assayed, including alkaline phosphatase, the deposit of calcium and protein levels of osteocalcin. Using miRNA microarray and reverse transcription-quantitative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…MicroRNAs including miR-31, miR-138, miR-204, and mir-637 have been investigated to inhibit osteogenic differentiation of BMSCs [105][106][107][108]. However, recently, Yan et al reported that let-7c-5p, miR-181c-3p, miR-3092-3p and miR-5132-3p promoted osteogenic differentiation of mouse BMSCs [109].…”
Section: Epigenetic Factors Involved In Osteogenic Differentiation Ofmentioning
confidence: 99%
“…MicroRNAs including miR-31, miR-138, miR-204, and mir-637 have been investigated to inhibit osteogenic differentiation of BMSCs [105][106][107][108]. However, recently, Yan et al reported that let-7c-5p, miR-181c-3p, miR-3092-3p and miR-5132-3p promoted osteogenic differentiation of mouse BMSCs [109].…”
Section: Epigenetic Factors Involved In Osteogenic Differentiation Ofmentioning
confidence: 99%
“…BMSC osteogenesis is the key step in bone regeneration and is affected by several factors including hormones, growth factors, environmental factors, and microRNAs [11]. BMSCs not only give rise to bone tissues but can also differentiate into adipose cells or osteoblasts [60].…”
Section: Role Of Bmscs In Bone Regenerative Therapymentioning
confidence: 99%
“…Therefore, the current focus of treating bone disorders is tissue regeneration using bone marrow mesenchymal stem cells (BMSCs) [7, 8]. A number of studies have investigated the effects of various drugs, mechanical stress, physical stimuli, and scaffolds on BMSCs [9–11], in order to clinically translate its regenerative capacity [12]. Traditional Chinese medicine (TCM) has also garnered considerable interest in recent years due to its minimal toxicity [13].…”
Section: Introductionmentioning
confidence: 99%
“…In support of our results, four of the six miRNAs ( miR-449a , miR-378a , miR-344 , and miR-874 ) have already been implicated in regulating insulin signaling, improving metabolic dysregulation, and activating insulin synthesis[ 35 - 38 ]. The other two miRNAs ( miR-5132-3p and miR-3075) have been suggested to play a regulatory role in the proliferation and migration of osteoblasts and Schwann cells[ 39 , 40 ]. Hence, we propose that miR-5132-3p and miR-3075 may act as new effector molecules in β-cell regulation.…”
Section: Discussionmentioning
confidence: 99%